STAT1 Regulates the Homeostatic Component of Visual Cortical Plasticity via an AMPA Receptor-Mediated Mechanism - Nagakura, Ikue (Society for Neuroscience, 2014)
Accumulating evidence points to a role for Janus kinase/signal transducers and activators of transcription (STAT) immune signaling in neuronal function; however, its role in experience-dependent plasticity is unknown. Here we show that one of its components, STAT1, negatively regulates the homeostatic component of ocular dominance plasticity in visual cortex. After brief monocular deprivation (MD), STAT1 knock-out (KO) mice show an accelerated increase of open-eye responses, to a level comparable with open-eye responses after a longer duration of MD in wild-type (WT) mice. Therefore, this component of plasticity is abnormally enhanced in KO mice. Conversely, increasing STAT1 signaling by IFNγ treatment in WT mice reduces the homeostatic component of plasticity by impairing open-eye responses. Enhanced plasticity in KO mice is accompanied by sustained surface levels of GluA1 AMPA receptors and increased amplitude and frequency of AMPA receptor-mediated mEPSCs, which resemble changes in WT mice after a longer duration of MD. These results demonstrate a unique role for STAT1 during visual cortical plasticity in vivo through a mechanism that includes AMPA receptors.